2020
DOI: 10.24095/hpcdp.40.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory HIV screening, migration and HIV stigma in Canada: exploring the experiences of sub-Saharan African immigrants living with HIV in western Canada

Abstract: Introduction In this mixed-methods pilot study, we examined the intersections of the current Canadian immigration policy, mandatory HIV screening during the Immigration Medical Exam (IME) and enacted and internalized stigma for HIV-positive immigrants from sub-Saharan Africa (SSA) in a western Canadian province. We focus on qualitative findings from this study. Methods Using the Internalized HIV Stigma Scale (IHSS), we collected data from eight immigrants from SSA liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
3
11
0
1
Order By: Relevance
“…After individual-level barriers, an inadequate clinical environment appeared to be the largest threat to retention in HIV care and treatment. 56 , 61 , 65 , 66 , 68 , 70 , 71 , 73 , 77 , 78 , 80 , 83–85 , 90 , 94 , 100 , 102 , 105 , 112 Several factors determined the inadequacy of a clinical environment for MLWH. Lack of space and capacity were associated with increased numbers of patients in clinics and thereby longer waiting times.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After individual-level barriers, an inadequate clinical environment appeared to be the largest threat to retention in HIV care and treatment. 56 , 61 , 65 , 66 , 68 , 70 , 71 , 73 , 77 , 78 , 80 , 83–85 , 90 , 94 , 100 , 102 , 105 , 112 Several factors determined the inadequacy of a clinical environment for MLWH. Lack of space and capacity were associated with increased numbers of patients in clinics and thereby longer waiting times.…”
Section: Resultsmentioning
confidence: 99%
“…Failure to give MLWH sufficient or tailored information is likely to hinder linkage. 71,85 In addition, one study reported that women could be linked to HIV care through pregnancy and childcare services, while men appeared to lack a comparable front door to care. 65 Community-level barriers.…”
Section: Barriers-linkagementioning
confidence: 99%
“…Immigration applicants living with HIV experience stigma within the Canadian IME, migration, and settlement process ( dela Cruz et al., 2020 ). Stigma is defined as an undesirable attribute of an individual that affects the person's status in society ( Goffman, 1963 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, dela Cruz and colleagues ( dela Cruz, 2014 ) found that many immigration applicants did not recall receiving any pre-test counseling, and thus were not even aware that they had been tested when they received their HIV-positive diagnosis during the IME. In another study, immigration applicants reported insensitive, flippant and cursory post-test counseling, leaving people with a sense of shame, fear and apprehension about their health and immigration prospects ( dela Cruz et al., 2020 ). Furthermore, participants rarely recalled receiving any advice, referrals or even reassurance from IME physicians about accessing treatment in Canada.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation